Arduino for beginners : 2022 complete course. (Packt Publishing, 2022)
Want to learn Arduino in a fun, practical, and efficient way? Don't wait anymore and start your Arduino journey with this complete course today. About This Video Become confident to create your own Arduino projects Install an Arduino library with different versions Communicate between your Arduino and your computer through Serial In Detail This course helps you start from scratch and get the necessary foundation you need and learn--through practice and hands-on lessons--the complete process to create Arduino projects. The course is divided into four main parts. First, you will set up the Arduino IDE (or the free online simulator), create your own circuit, learn the Arduino programming fundamentals, and understand and work with digital/analog pins to control Land EDs, push buttons, and potentiometers. After this "basic Arduino foundation" package, it's time to get to know new Arduino functionalities to go further with your projects: time, multitasking, debounce, interrupts Serial, EEPROM. Now you will be more confident to create any Arduino program or project. Here, you will work with new hardware components such as an ultrasonic sensor, LCD display screen, infrared remote controller, and photoresistor. To finish, a big final project: an interactive obstacle detection application. You will get a nice challenge to create a real and useful Arduino project, which you can reuse and modify for your own purpose. By the end of this complete course, you will have a strong Arduino foundation and you will be able to start any custom Arduino project that you want. Audience This course can be taken by students, engineers, researchers, teachers, and developers. It is also useful for software developers who want to discover the electronics/hardware world; anyone who has a hardware project idea and wants to bring it to the world; and anyone who wants to use fast prototyping for a hardware product using Arduino. No prior knowledge is required in Arduino, programming, hardware, or engineering.